SEGREGATION PATTERNS OF CDNA-BASED MICROSATELLITE AND RAPD-PCR MARKERS IN F2 INDIVIDUALS OF CAPSICUM ANNUUM L. - Ince, Ayse Gul; Karaca, M.; Onus, A. Naci (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Recently in our laboratories we obtained surprising results in which our analyses indicated that some of the cDNA-based microsatellite primer pairs amplified polymorphic markers within different tissue, organ and development stage specific cDNA libraries of Capsicum annuum L. Demre Sivrisi (DS) variety. Based on these findings, we hypothesized whether tissue organ specific microsatellite could be used in mapping studies. Forty F2 individual progenies were generated from a cross between DS and Capsicum annuum L. PM687 lines with aims to compare segregation patterns and polymorphism information contents of DNA markers using random amplified polymorphic DNA (RAPD-PCR), as a control, and cDNA based microsatellite polymorphism. A total of 30 expressed sequence tags (EST) based primer pairs and 30 RAPD-PCR primers were used in the amplification of genomic DNAs of the parental lines and the individual F2 progenies of DS X PM687. Segregation patterns, inheritance of the loci [dominant (3:1) or co-dominant (1:2:1)] were determined using the chi-square analyses. Analyses indicated that 6 RAPD-PCR and 4 EST microsatellite markers were polymorphic between the parental lines and among the F2 individuals. Polymorphism information contents of cDNA-based microsatellite markers were higher than RAPD-PCR markers. One of the 6 RAPD-PCR primers produced co-dominant loci while cDNA-based microsatellite primer pairs produced 3 co-dominant loci. Results indicated that cDNA-based microsatellite markers do segregate according to Mendelian law as that of the conventional genomic DNA based microsatellites indicating that cDNA-based microsatellites can be safely used in genetic mapping and diversity studies.